2022
DOI: 10.3390/e24121803
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Mode Decomposition Fuzzy Forecast Model for Air Quality

Abstract: Air quality has a significant influence on people’s health. Severe air pollution can cause respiratory diseases, while good air quality is beneficial to physical and mental health. Therefore, the prediction of air quality is very important. Since the concentration data of air pollutants are time series, their time characteristics should be considered in their prediction. However, the traditional neural network for time series prediction is limited by its own structure, which makes it very easy for it to fall i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Composite air quality prediction frameworks, integrating various machine learning and deep learning models, have shown even more promising outcomes. For example, combining long short-term memory networks with Gated Recurrent Unit model [27], random subspace [28], attention mechanism [29], XGBoosting tree [30], random forest regression based on linear regression [31], and an adaptive fuzzy inference system with the Extreme Learning Machine [32] has yielded substantial advancements. Phruksahiran, N [33] introduced the Geographically Weighted Prediction Method (GWP), leveraging optimal machine learning algorithms and additional prediction variables.…”
Section: Introductionmentioning
confidence: 99%
“…Composite air quality prediction frameworks, integrating various machine learning and deep learning models, have shown even more promising outcomes. For example, combining long short-term memory networks with Gated Recurrent Unit model [27], random subspace [28], attention mechanism [29], XGBoosting tree [30], random forest regression based on linear regression [31], and an adaptive fuzzy inference system with the Extreme Learning Machine [32] has yielded substantial advancements. Phruksahiran, N [33] introduced the Geographically Weighted Prediction Method (GWP), leveraging optimal machine learning algorithms and additional prediction variables.…”
Section: Introductionmentioning
confidence: 99%
“…The RF + BP + GA model has the best fitting effect among the air quality-meteorology correlation models, basically achieves complete fitting, and can accurately predict the AQI value of air quality. Jiang et al [45] established the fusion model of the limit gradient lifting algorithm + BP + autoregressive moving average model to jointly predict the air quality in Changping District, Beijing. They found that the prediction effect of the proposed model was more accurate than the air quality prediction of a single limit gradient lifting algorithm, BPNN, or autoregressive moving average model.…”
Section: Discussionmentioning
confidence: 99%
“…Time series generally refers to a set of random variables derived from the observation of the development and change process of something and collected at a certain frequency, with characteristics of time dependency, seasonality, trend, and randomness. Time series forecasting is vital in many real-world scenarios, such as traffic forecasts [ 1 , 2 ], air quality prediction [ 3 , 4 , 5 ], and water quality monitoring [ 6 ]. Especially in the field of healthcare, the forecasting of future incidence and mortality rates among patients enables effective control and prevention of diseases [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%